Structural Behavior of Concrete Filled Aluminum Tubular Columns - Nasser, Kadhim Zuboon (Basrah Journal for Engineering Sciences, 2012)
The paper presents an experimental and theoretical study on the behavior of circular concrete filled aluminum tubular columns. The main purpose of the experimental program was to investigate the structural behavior of aluminum-concrete composite columns under axial compression loading conditions. Twenty four specimens were tested to investigate the effect of diameter, D/t ratio and slenderness ratio of a aluminum tube on the load carrying capacity of the concrete filled tubular columns. Diameter to wall thickness ratio ranged between 11.9 ≤ D/t ≤ 22.8, and the length to tube diameter ratios of 3 ≤ L/D ≤ 10 were investigated. The main purpose of the theoretical investigation was to predict the strength of aluminum -concrete composite columns subjected to axial compression loading conditions. The empirical equations proposed in the present study are capable of predicting the values of ultimate loads of aluminum -concrete composite columns and were in good agreement with the experimental values. The average values of ratios of experimental to predicted values of ultimate loads are 1.0104 for the proposed empirical equations. The circular hollow section tubes were fabricated by extrusion using 6061-T6 heat-treated aluminum alloy. The column strengths, load-axial shortening relationship and failure modes of columns were presented.